STUDENTS’ AND TEACHER’S PERCEPTION ON SPEAKING CLASSROOM ACTIVITIES THROUGH ROLE-PLAY FOR EIGHTH GRADE STUDENTS AT SMP NEGERI 35 MEDAN - Vanny Salsabillah; Safrida Lubis (Jurnal Scientia, 2023)
This study investigated in eighth grade students at SMP Negeri 35 Medan for students' and teacher's perceptions of Role-Play speaking classroom activities. Using questionnaires, and interviews, data was collected from 31 students and an English teacher. The method used Mix Method Research (MMR) to calculated the data. The results indicated that 86.5% of students believed that role-playing was effective for enhancing speaking abilities and from the teacher's perception stated role-play was good to be used in to learning for speaking activity. The study discovered that role-playing was effective at encouraging students to improve their speaking skills. The use of images on paper as a role-play media was also found to be simple to comprehend and to facilitate classroom activities. Overall, this research discovered that role-play was beneficial and effective for improving students' speaking abilities.